Women's movements and the Filipina, 1986-2008 - Roces, Mina 1959- (University of Hawaiʻi Press, 2012)
This work explores a fundamental aspect of the feminist project in the Philippines: rethinking the Filipino woman. It focuses on how contemporary women's organisations have represented and refashioned the Filipina in their campaigns to improve women's status by locating her in history, society and politics; imagining her past, present and future; representing her in advocacy; and identifying strategies to transform her.